Research on hybrid propulsion system with parallel power configuration: theory and experiment based on dynamics - Xu, Jianghai; Xue, Lin; Zou, Donglin; Ta, Na; Rao, Zhushi (Nonlinear dynamics, 2024)
With the increasingly serious problems of international energy shortage and environmental degradation, the adoption of hybrid energy forms represents an effective solution to these challenges and has been widely implemented in the propulsion systems of aircraft, vehicles, and ships. For the hybrid propulsion system with parallel power configuration, a comprehensive investigation has been conducted to understand the system’s dynamic characteristics and the evolution laws associated with power parameters. By appropriately simplifying of the actual propulsion system, a nonlinear dynamic model with multi-factor and multi-degree-of-freedom (multi-DOF) coupling is established. The dynamic equations are solved by numerical method, and the motion state of the system under various rotating speeds is revealed through global and local characteristic analyses. The evolution laws of the dynamic characteristics are studies with respect to different combinations of key power parameters, including ( λ ω , λ f ) and ( f o , λ f ), and the impact of these parameters on the system stability is discussed. Finally, an experimental platform with a parallel drive system is established to quantitatively assess the effects of rotating speed and torque ratio on frequency response, dynamic characteristics, and power efficiency. The results indicate that low rotating speed, heavy load, and large torque ratio have positive implications for the stability of the propulsion system. However, an excessively low torque ratio can significantly compromise power efficiency. It is anticipated that this research will serve as a valuable reference for the design of dynamic stability and optimization of the power configuration in hybrid propulsion systems.